Magnetic Properties of a Holocene Sediment Core from the Yeongsan Estuary, Southwest Korea: Implications for Diagenetic Effects and Availability as Paleoenvironmental Proxies - Ahn, Hyeon–Seon; Lim, Jaesoo; Kim, Sung Won (Frontiers in Earth Science, 2021)
The sensitivity of magnetic properties, which characterize the mineralogy, concentration, and grain size distribution of magnetic minerals, to environmental processes may provide useful information on paleoenvironmental changes in estuarine environments. Magnetic property studies of estuaries are less common than other environments and, due to the west coast of South Korea having an abundance of estuaries, it provides a good place to study these processes. In this study, we analyzed a variety of magnetic properties based on magnetic susceptibility, hysteresis parameters, progressive acquisition of isothermal remanent magnetization and first-order reversal curve data from a Holocene muddy sediment core recovered from the Yeongsan Estuary on the west coast of South Korea. We examined diagenetic effects on magnetic properties and tested their availability as proxies of paleoenvironmental change. The presence of generally low magnetic susceptibility, ubiquitous greigite-like authigenic magnetic component, and very fine magnetic particle occurrence suggested that the analyzed sediments had undergone considerable early diagenetic alteration. Electron microscopic observations of magnetic minerals support this suggestion. Our results confirm that the use of initial bulk susceptibility as a stand-alone environmental change proxy is not recommended unless it is supported by additional magnetic analyses. We recognized the existence of ferromagnetic-based variabilities related to something besides the adverse diagenetic effects, and have examined possible relationships with sea-level and major climate changes during the Holocene. The most remarkable finding of this study is the two distinct intervals with high values in magnetic coercivity (Bc), coercivity of remanence (Bcr), and ratio of remanent saturation moment to saturation moment (Mrs/Ms) that were well coincident with the respective abrupt decelerations in the rate of sea-level rise occurred at around 8.2 and 7 thousand years ago. It is then inferred that such condition with abrupt drop in sea-level rise rate would be favorable for the abrupt modification of grain size distribution toward more single-domain-like content. We modestly propose consideration of the Bc, Bcr, and Mrs/Ms variability as a potential indicator for the initiation/occurrence of sea-level stillstand/slowstand or highstand during the Holocence, at least at estuarine environments in and around the studied area.